Holy, Wholly, Holey: Ecclesiastes 4:17–5:6 in Text and Tradition - Hankins, Davis (The catholic biblical quarterly, 2024)
This interpretation of Eccl 4:17-5:6 (Eng. 5:1-7) challenges a common scholarly conclusion--that Qoheleth emphasizes divine transcendence. Qoheleth’s articulation of divine transcendence may initially seem clear: "God is in the heavens and you are on the earth" (5:1). But this statement appears within a tightly structured passage that focuses squarely on human attempts to relate to God and various problems that beset such attempts. We offer a novel formal analysis of this pericope, demonstrating that it describes the religious consequences of the distance that separates what people say from what they do. This distance between human words and human deeds underlies Qoheleth’s counsel against certain rituals and religious practices, as well as his commendation at the end of the passage to "fear God," and thus may be understood as the distance between earth and heaven that Qoheleth asserts in 5:1. In this passage’s reception history, we find three distinct interpretative trajectories, which we indicate with the three homonyms in the title. Some interpretations affirm God’s heavenly, holy transcendence, whereas others, perhaps surprisingly, view this text as affirming God’s immanence on earth. A third interpretation considers instead the limits and fractures of human life on earth as manifestations of the heavenly divine. While most interpretations of this passage align with the first or second readings, we argue that the third trajectory aligns most closely with Qoheleth’s teachings.